1974
DOI: 10.1001/archpedi.1974.02110200110017
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer (Squamous Cell Carcinoma) in Adolescence

Abstract: Primary lung cancer is rare in childhood. An asymptomatic 15-year-old boy was found to have a solitary circular shadow by a mass chest photofluorographic survey. The clinical course strongly suggested malignant tumor. Lobectomy three months after the detection of the shadow showed squamous cell carcinoma. At present, 3\m=1/2\years after surgery, the patient is healthy and attending school. Cases of primary lung cancer in childhood are reviewed.While the frequency of primary carcinoma of the lung has re¬ cently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…2 In 1974, Niitu et al 5 reviewed 39 cases of primary lung tumors in chilAbbreviations AFB Acid-fast bacilli BAL Bronchoalveolar lavage CT Computed tomography NSE Neuron-specific enolase PPD Purified protein derivative SCBC Small cell bronchogenic carcinoma dren younger than 16 years of age and found that bronchogenic carcinoma accounted for 17 cases, including 12 cases of adenocarcinoma and 5 cases of squamous cell carcinoma. In 1983, Hartman and Shochat 3 reviewed 230 cases of primary lung tumors in children under 16 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…2 In 1974, Niitu et al 5 reviewed 39 cases of primary lung tumors in chilAbbreviations AFB Acid-fast bacilli BAL Bronchoalveolar lavage CT Computed tomography NSE Neuron-specific enolase PPD Purified protein derivative SCBC Small cell bronchogenic carcinoma dren younger than 16 years of age and found that bronchogenic carcinoma accounted for 17 cases, including 12 cases of adenocarcinoma and 5 cases of squamous cell carcinoma. In 1983, Hartman and Shochat 3 reviewed 230 cases of primary lung tumors in children under 16 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in children, it is reported that squamous cell carcinomas is 21 %, adenocarcinomas 32 %, and undifferentiated carcinomas 28 % (11). In the study for child lung cancer in foreign countries, squamous cell carcinoma account 10 %, and adenocarcinoma is 28 %, and undifferentiated carcinoma account 45 % (12). It is thus likely that squamous cell carcinoma is less frequently found in children than in adults.…”
Section: Breast Breastmentioning
confidence: 99%
“…A rate of 20% for squamous carcinoma has been reported in Japan and 10% in other countries. 52 They concede that bronchogenic squamous carcinoma could possibly occur in children less than 12 years of age and appeal for such tumors to be studied with great care before being validated as such. In one case of childhood pleural mesothelioma prenatal exposure to isoniazid has occurred.…”
Section: Capillary Hemangiomamentioning
confidence: 99%